Dry mouth effects from drugs used for depression, anxiety, schizophrenia and bipolar mood disorder in adults: systematic review. Issue 2 (20th March 2023) - Teoh, Cherilyn Xue Wei; Thng, Millie; Lau, Serene; Taing, Meng-Wong; Chaw, Sarah Y.; Siskind, Dan; Kisely, Steve
Abstract : Background: Poor oral health is increasingly recognised as an important comorbidity in people with psychiatric illness. One risk factor is psychotropic-induced dry mouth. Aims: To perform a systematic review of the severity of dry mouth due to psychotropic drugs in adults (CRD42021239725). Study quality was assessed using the Cochrane risk of bias tool. Method: We searched the following databases: PubMed, EMBASE, PsycINFO, Cochrane Central Register of Controlled Trials, CINAHL and Web of Science. We included randomised controlled trials (RCTs) measuring the severity of drug-induced hyposalivation and xerostomia. Results: Eighteen RCTs with 605 participants were included. Severity of drug-induced dry mouth was compared among eight drug classes and/or against placebo. All studies were published 20 to 40 years ago and included tricyclic antidepressants (TCAs), serotonin specific reuptake inhibitors (SSRIs) and other drug classes. Meta-analysis was not feasible owing to design heterogeneity. TCAs caused more severe dry mouth, both objectively and subjectively, than placebo or other drug classes. SSRIs were generally associated with less severe symptoms. However, there was no information on antipsychotics or more recently available antidepressants, and there was minimal information on mood stabilisers. Most studies were on healthy subjects, limiting the generalisability of findings. Only one study measured both objective and subjective dry mouth, which have different clinical implications. Conclusions: Psychotropic-induced dry mouth is a poorly researched area, and well-designed RCTs of newer psychotropic drugs using standardised objective and subjective measures are indicated. Given the ongoing use of TCAs for treatment-resistant depression, prescribers need to remain vigilant for xerostomia.